2013
DOI: 10.1016/j.jcdr.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omega-3 on brain natriuretic peptide and echocardiographic findings in heart failure: Double-blind placebo-controlled randomized trial

Abstract: a b s t r a c tBackground: Possible beneficial effects of dietary omega-3 supplementation on patients with congestive heart failure (CHF) were investigated. Methods and results: 100 patients with CHF who had a tri-chamber pacemaker and automated defibrillator were initially recruited, and 70 agreed to participate.38 patients received 2 g/day of omega-3 and 32 received placebo capsules. BNP level, 6-min walk test and echocardiographic parameters were recorded at baseline and after 6 months of treatment. BNP lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 27 publications
(19 reference statements)
0
22
1
2
Order By: Relevance
“…The remaining studies were nine clinical trials [ 11 , 12 , 14 , 17 , 18 , 19 , 20 , 21 , 22 ] and included a total of 800 patients, as described in Table 1 and Table 2 . All nine studies were RCT designs published from 2006 to 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining studies were nine clinical trials [ 11 , 12 , 14 , 17 , 18 , 19 , 20 , 21 , 22 ] and included a total of 800 patients, as described in Table 1 and Table 2 . All nine studies were RCT designs published from 2006 to 2016.…”
Section: Resultsmentioning
confidence: 99%
“…A previous meta-analysis performed in 2012 [ 10 ] indicated that omega-3 PUFAs could improve cardiac function and functional capacity in HF patients. However, since the publication of that analysis, there have been many new clinical trials about the effect of omega-3 PUFAs in HF patients with different outcomes and inconsistent results [ 11 , 12 , 13 , 14 ]. For this reason, to assess a greater number of studies and more comprehensively determine the benefits of omega-3 PUFAs in HF patients, we performed a meta-analysis of randomised controlled trials (RCTs) to systematically evaluate the effects of omega-3 PUFAs in HF patients.…”
Section: Introductionmentioning
confidence: 99%
“…In mehreren Interventionsstudien wurde die echokardiographisch gemessene linksventrikuläre Auswurffraktion sowie andere echokardiographische Parameter der Herzfunktion durch die Gabe von EPA und DHA gebessert [17,22,18,26,14]. Im Rahmen von GISSI-HF wurde die echokardiographisch gemessene linksventrikuläre Auswurffraktion über die drei Studienjahre von Jahr zu Jahr besser [14].…”
Section: Besserung Der Linksventrikulären Funktionunclassified
“…Im Rahmen von GISSI-HF wurde die echokardiographisch gemessene linksventrikuläre Auswurffraktion über die drei Studienjahre von Jahr zu Jahr besser [14]. Passend dazu besserte sich, wenn gemessen, der maximale Sauerstoffverbrauch, zudem senkte sich der Plasma brain natriuretic peptide, die Trainingsdauer verlängerte sich, zudem konnte die Strecke im 6-Minuten-Gehtest verlängert werden [18,26]. Wenn gemessen, besserte sich auch die Endothelfunktion [22].…”
Section: Besserung Der Linksventrikulären Funktionunclassified
“…21 In the Alpha-Omega Trial, low-dose nutritional supplementation with 400 mg EPA-DHA (3:2 ratio) per day was shown not to reduce the rate of major cardiovascular events among postinfarct patients who received other state of the art antihypertensive, antithrombotic, and lipid-modifying therapy 22 ; also, no effect on N-terminal prohormone of Btype natriuretic peptide was found in a subpopulation of this study, 23 whereas treatment with 2 g omega-3 fatty acids per day for 6 months was associated with a reduction of BNP. 24 In the preceding Gruppo Italiano per lo Studio della Sopravvivenza nell'Insufficienza cardiaca-Heart Failure (GISSI-HF) trial 3 in heart failure patients with reduced LVEF irrespective of cause, and in the Gruppo Italiano per lo Studio della Sopravvivenza nell'Insufficienza cardiaca (GISSI)-Prevenzione trial in patients with myocardial infarction, 2 1 g omega-3 HUFA per day reduced mortality and hospitalization. 25 benefit.…”
Section: Hufa Deficiency In Heart Failurementioning
confidence: 99%